The Effect of Trading Frequency, Value, and Volume on Capital Investment Decision Making in the Capital Market that is Indicted by Jakarta Islamic Index (JII) - Basrowi; Fauzi (Journal of Asian Business Strategy, 2019)
Business people have many considerations when making decisions to make capital investments, mainly because of various considerations of risk that will be accepted both now and in the future. Predictions to obtain maximum profits are also a major consideration. Specifically, the purpose of this study is to predict the effects of frequency of trading, the volume of trade, and value trading when making capital investment decisions, not only in large part but also simultaneously. Secondary data was obtained using data that was already available on the IDX, especially issuers indexed in the Jakarta Islamic Index (JII), which were then obtained in accordance with the problem formulation. The data was approved until January 2017 to December 2018. The results of the analysis convinced the author, the fact of trade affects investment decisions, trading volume is also able to influence investment decisions, and the value of trade also greatly influences investment returns. Cumulative trading frequency, trading volume, and value trading also influence capital investment decision making at JII.